Intrauterine Foetal Death and Its Probable Causes: Two Years Experience in Dhulikhel Hospital – Kathmandu University Hospital - Tamrakar, SR; Chawla, CD (Kathmandu University Medical Journal, 2014)
Background World health Organization definition of intrauterine foetal demise encompasses any abortion or fetal demise prior to expulsion from its mother, and recommends different protocols according to gestational age. However, conventionally and also in our institution, foetal demise prior to 28 weeks of gestation is managed as abortion in a manner different from foetal demise post 28 weeks of gestation. Objective To find the incidence and characteristics of pregnancies that resulted in stillbirths. Methods A retrospective study, done in Dhulikhel Hospital, Kathmandu University Hospital in the year 2010 and 2011, among 4219 deliveries and 97 fetal deaths. Cases of multiple pregnancy and fetal death diagnosed by ultrasound before the 28th week of gestation were excluded. The included intrauterine foetal demise cases (n=90) were compared with a control group of randomly selected pregnancies (n = 537) delivered during the same time period. Assumed predictors of stillbirth were examined through inferential ways (Chi square, t test) using SPSS Version 13.0 for Windows. Results Incidence of intrauterine foetal demise was 2.13% in the year 2010 and 2011. Mothers in the stillbirth group were slightly older than mothers of live-born infants (25.47±5.64 years vs 23.62±4.31 years, p value=0.000). A slightly higher proportion of women in the stillbirth group were of Tamang ethnic origin and primiparous (p = 0.011, 0.000) . Foetus expelled after IUFD had lower weight compared to live births, (2925.14±444.14gram vs 2182.78±821.04gram, p=0.000) for gestational age. The stillborn babies were generally born at an earlier gestational age, as would be expected (p=0.000). Incidence of intrauterine foetal demise gradually decreases as parity advances. The incidence was higher in patients receiving antenatal care outside Dhulikhel Hospital, Kathmandu University Hospital. Conclusions While comparing the subject with the theme of the national conference of Nepal Society of Obstetricians and Gynaecologist, most of the cases were mother not receiving antenatal care or those receiving antenatal care in the periphery, There is no denying that there would be a massive improvement in women’s health if the co-ordination between the peripheral health care center and tertiary care center was to be improved. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10994 Kathmandu Univ Med J 2012;10(4):44-48